SOME PARALLELS IN THE WORKS OF AKAKI TSERETELI AND ADAM MITSKEVICH - Manana Kajaia (European Scientific Journal, ESJ, 2014)
This paper presents research on the closeness of poetic world that developed between most prominent poets Akaki Tsereteli and Adam Mitskevich. Namely, an emphasis is placed on spiritual closeness of Georgian and Polish peoples. Some general parallels between Akaki Tsereteli’s poem Bagrat the Great and Adam Mitskevich’s poem Konrad Wallenrod which intensify patriotic spirit are extensively considered in the work. A review of existing scholarly literature is presented and conclusions based on biographical data of two great creators are offered.